2006
DOI: 10.1093/bja/aei299
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar recruitment in acute lung injury

Abstract: Alveolar recruitment is one of the primary goals of respiratory care for acute lung injury. It is aimed at improving pulmonary gas exchange and, even more important, at protecting the lungs from ventilator-induced trauma. This review addresses the concept of alveolar recruitment for lung protection in acute lung injury. It provides reasons for why atelectasis and atelectrauma should be avoided; it analyses current and future approaches on how to achieve and preserve alveolar recruitment; and it discusses the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 121 publications
(60 reference statements)
3
76
1
3
Order By: Relevance
“…Furthermore, development of techniques for direct bedside monitoring of alveolar dynamics would be a major step forward in clinical ventilator management (20).…”
Section: Clinical Relevancementioning
confidence: 99%
“…Furthermore, development of techniques for direct bedside monitoring of alveolar dynamics would be a major step forward in clinical ventilator management (20).…”
Section: Clinical Relevancementioning
confidence: 99%
“…It is believed that the use of these strategies in clinical practice determines an important reduction of morbidity and mortality [19,20].…”
Section: Indicationsmentioning
confidence: 99%
“…PEEP provides higher alveolar stability after the recruitment. The ideal PEEP can be determined by the best gas exchange point, in other words, 2 cmH2O above the lower inflection point of pressure-volume curve of the respiratory system, observing the hemodynamic stability [10,20,26 Benefits Studies have shown that alveolar recruitment strategies can improve respiratory function in the postoperative period of cardiac surgery by reducing atelectasis and intrapulmonary shunt, improving ventilation-perfusion ratio and, consequently, arterial oxygenation [11,13,16].…”
Section: Adverse Effects and Contraindicationsmentioning
confidence: 99%
“…Ventilator settings are often adjusted to achieve predestined arterial blood gas tensions. This approach is adequate with respect to oxygenation and carbon dioxide elimination [4].…”
Section: Introductionmentioning
confidence: 99%